Progressive Muscle Relaxation and Benson Therapy in Reducing Anxiety in Breast Cancer Patients - Rusmiyati Rusmiyati; Ellyzabeth Sukmawati; Dayat Trihadi; Achmad Solechan; Dias Choirun Nisa (Jurnal Bidan Cerdas, 2025)
Background: This study aimed to examine the effect of non-pharmacological therapy, specifically progressive muscle relaxation and Benson relaxation, on anxiety levels in breast cancer patients undergoing chemotherapy. Chemotherapy is known to trigger psychological disorders, including anxiety, which can negatively affect treatment outcomes. Methods: A pre-experimental design with a one-group pretest–posttest approach was applied, involving 43 purposively selected respondents. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS). Results: The majority of respondents were aged 46–55 years, had completed high school or vocational school, were unemployed, and had undergone chemotherapy 1–6 times. The Wilcoxon signed-rank test revealed a significant reduction in anxiety scores after the intervention. Conclussion: These findings indicate that progressive muscle relaxation and Benson relaxation are effective in reducing anxiety among breast cancer patients undergoing chemotherapy, highlighting the importance of integrating non-pharmacological interventions into supportive oncology care.